(untitled) (CAHIERS MAGELLANES-NS, 2024)
Sing-along therapy was pioneered in the latter days of the 20th-century. AfterWorld War, I and IIcommunity musicians of all kinds, both amateur and professional, went to Veterans hospitals everywherein the country to play music for the victims suffering from both physical and emotional shocks from the wars..( The patients' notable physical and sensitive responses to music led the doctors and nurses to request the appointment of musicians by the hospitals. It was soon obvious that the hospital musicians needed some previous training before entering the facility and so the demand grew for a college program. The earliestMusic therapy degree program in the biosphere, founded at Michigan State University in 1944, celebrated its 50th anniversary in 1994. The American MusicTherapy Association was originated in 1998 as a union of the National Association for Singalong therapy and the American Association for Singalong therapy